2017
DOI: 10.1088/1361-648x/aa5532
|View full text |Cite
|
Sign up to set email alerts
|

Site dilution in SrRuO3: effects on structural and magnetic properties

Abstract: We have investigated the effect of site dilution with substitution of nonmagnetic element in SrRu Ti O (x  ⩽  0.7). The nature of ferromagnetic state in SrRuO is believed to be of itinerant type with transition temperature [Formula: see text] K. Crystallographically, SrRuO has a distorted orthorhombic structure. Substitution of [Formula: see text] (3d ) for Ru (4d ), however, does not introduce significant structural modification due to their matching ionic radii. This substitution, on the other hand, is expec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 40 publications
5
33
0
Order By: Relevance
“…The details of samples preparation and characterization of ingredients and temperature used have been discussed elsewhere. [13,14] Temperature and field dependent magnetic measurements have been done using SQUID. Further, the dc electrical resistivity ρ(T ) and magnetoresistance (MR) data are collected using a home-built setup attached with Oxford superconducting magnet by following the four probe technique, in the temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The details of samples preparation and characterization of ingredients and temperature used have been discussed elsewhere. [13,14] Temperature and field dependent magnetic measurements have been done using SQUID. Further, the dc electrical resistivity ρ(T ) and magnetoresistance (MR) data are collected using a home-built setup attached with Oxford superconducting magnet by following the four probe technique, in the temperature.…”
Section: Methodsmentioning
confidence: 99%
“…While for the Co substitution in our SBRCO and SRCO sample, both the magnetic moment and T c decreases. In the previous study reported by Gupta et al,24 with Ti substitution at Ru site, the magnetic moment decreases but T c remains unchanged. Among the previously other doped transition metal such as Mn, 25 Fe, 26 and Cr 27 etc., the enhancement of T c is only for Cr substitution.…”
Section: -7mentioning
confidence: 69%
“…32 In SrRu 1−x Ti x O 3 , the T C remains unchanged with Ti substitution, whereas Weiss temperature and magnetic moment continually decreases. 33 Because of the similar ionic radius of Ru 4+ (0.62 Å) and Sn 4+ (0.69 Å) ions, 34 Sn doping at Ru site in SRO is quite feasible. It has been reported that the epitaxial SrRu 0.48 Sn 0.52 O 3 thin film exhibits an excellent lattice match with (100)-oriented KTaO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The substitution of Mn ions for Ru ions causes many interesting physical phenomena, such as FM, spin‐glass, anti‐FM, and mixed‐valent behavior 32 . In SrRu 1− x Ti x O 3 , the T C remains unchanged with Ti substitution, whereas Weiss temperature and magnetic moment continually decreases 33 …”
Section: Introductionmentioning
confidence: 99%